QUALITATIVE CONTENT ANALYSIS OF COMPLEMENTARY TOPICAL THERAPIES USED TO MANAGE DIABETIC FOOT IN JORDAN - Abu-Qamar, Ma’en Zaid; Wilson, Anne (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
In order to alleviate diabetic foot problems, patients sometimes seek complementary therapies outside the professional context. This paper describes the use of complementary remedies as a topical treatment for diabetic foot ulcers among Jordanians. Qualitative content analysis was used to analyse written responses of 68 patients with diabetes who have used complementary therapies to treat diabetic foot problems. These 68 persons represented a subgroup of the study population surveyed using a questionnaire, to the effect of investigating diabetic foot treatments provided in Jordan. Informants were recruited from eight healthcare facilities established in the southern part of Jordan plus from one hospital established in the Jordanian capital. The study was approved by the Boards of Ethics of the participating healthcare facilities. Content analysis yielded the category “Complementary Therapies Used”, which included a range of household items (olive oil, sesame oil, honey, and vinegar), and also some indigenous Jordanian herbs (Wormwood, Myrrh, Caper, and Henna among others). The remedies were used either as a monotherapy or as mixtures, to the common goal of treating diabetic foot problems. Other interventions like Al-cowy were also sought from traditional healers. Educational campaigns are required to increase the awareness of patients and their families on possible hazards of unwise complementary therapy use. The decisions on the use of such therapies should be made in agreement with the attending healthcare professionals.